Method and information technology for constructing a nonparametric dynamic model of the oculomotor system - Фомин, Александр Алексеевич; Моханад, Масри; Павленко, Виталий Данилович; Фёдорова, Анна Николаевна (Eastern-European Journal of Enterprise Technologies, 2015)
Method, information technology, computational algorithms and software tools for constructing a nonparametric dynamic model of the human oculomotor system were proposed. A method for constructing the nonparametric dynamic model of the human oculomotor system with regard to its inertia and nonlinear properties based on the data of experimental studies "input-output", as well as efficient computational algorithms and software tools for processing the data of identification experiments were developed. Nonparametric nonlinear dynamic model of the oculomotor system based on processing the data of experiment "input-output" - pupillary response to a disturbance in the form of a light spot was obtained. Using the algorithms for intelligent processing of the captured video sequence of the pupil position change, the function of the oculomotor system response to a disturbance is simulated. Description of the oculomotor system properties is made using the most versatile nonlinear nonparametric dynamic models in the form of Volterra series. The technology for tracking the pupil behavior using the video recording, which has allowed to determine the dynamic characteristics of the oculomotor system according to the observational data "input-output" have got further development. The proposed technology for tracking the pupil behavior is available for widespread use in modern applications with an expanded set of personalized features, such as medical and athletic training machines, authorized access to data, testing human-machine systems and so on. An important feature of the technology is indiscriminateness to the hardware that allows its use in the applications of modern mobile devices.